Analisis Komentar Netizen Terhadap Jersey Player Terbaru Timnas Indonesia yang Ditampilkan Melalui Foto dalam Akun Instagram @PSSI - Satriya Agung Prakoso; Nur Maghfirah Aesthetika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze netizen comments on the latest Indonesian National Team jersey posted through the official @pssi Instagram account. This research uses a qualitative approach with a content analysis method to identify the main themes that appear in netizen comments. Data were obtained from comments on Instagram posts featuring the new jersey. The results showed that netizen comments can be categorized into several main themes, namely support, design criticism, and national pride. Supportive comments generally appreciated the design of the jersey and considered it a symbol of national pride. Neutral comments often provide suggestions for improvement without clearly indicating a stance of support or opposition. Meanwhile, opposing comments expressed dissatisfaction with the jersey design, which was often attributed to unmet expectations. These findings provide insight into public perceptions of visual attributes associated with national identity in the context of social media. By paying attention to the input from netizens, PSSI can evaluate and improve the quality and design of the jersey in the future, so that it is more in line with public expectations. In addition, marketing strategies can be adjusted based on the trends and preferences identified in this analysis.